2015
DOI: 10.2217/bmt.15.13
|View full text |Cite
|
Sign up to set email alerts
|

Current and Future Methods for Measuring Breast Density: A Brief Comparative Review

Abstract: Breast density is one of the strongest predictors of breast cancer risk. Women with the densest breasts are 4 to 6 times more likely to develop cancer compared with those with the lowest densities. Breast density is generally assessed using mammographic imaging; however, this approach has limitations. Magnetic resonance imaging and ultrasound tomography are some alternative imaging modalities that can aid mammography in patient screening and the measurement of breast density. As breast density becomes more com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 101 publications
1
26
0
Order By: Relevance
“…Numerous epidemiologic studies conducted over the past four decades have consistently demonstrated that increased mammographic density is related to increased breast cancer risk (Huo, et al 2014, McCormack and dos Santos Silva 2006, Pettersson, et al 2014, Sak, et al 2015). It was determined that, when compared to women with lower densities, women with the highest mammographic densities showed a 4 to 6-fold increased risk of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous epidemiologic studies conducted over the past four decades have consistently demonstrated that increased mammographic density is related to increased breast cancer risk (Huo, et al 2014, McCormack and dos Santos Silva 2006, Pettersson, et al 2014, Sak, et al 2015). It was determined that, when compared to women with lower densities, women with the highest mammographic densities showed a 4 to 6-fold increased risk of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Mammographic percent density (MPD) is defined as the ratio of dense breast tissue relative to the total amount of breast tissue seen on a mammogram and is measured using computer-assisted programs such as Cumulus (Byng, et al 1994) or can be measured volumetrically using programs such as Volpara (Eng, et al 2014, Jeffreys, et al 2010) and Quantra (Ciatto, et al 2012, Regini, et al 2014). However, despite being the current gold standard for breast imaging, mammography poses some shortcomings for the measurement of breast density (Kopans 2008, Sak, et al 2015). …”
Section: Introductionmentioning
confidence: 99%
“…As such, improved imaging methods for quantifying breast tissue are desirable from a research and clinical perspective, offering improved understanding of breast cancer and patient care. 5,[11][12][13] However, there is a major barrier to quantitative characterization of breast cancer; biomedical imaging has an inverse relation between the volume any imaging modality can cover (field of view and penetration depth) and the size of details it can visualize (spatial resolution). [14][15][16] Due to this, clinical imaging modalities are often restricted to a single range for the combined resolution, field of view, and penetration depth (the spatial scale).…”
Section: Review Of Quantitative Multiscale Imaging Of Breast Cancer 1mentioning
confidence: 99%
“…We mention, but do not extensively cover, clinical imaging, as there are many excellent reviews on clinical imaging of the breast. 12,46,[49][50][51] Finally, the review describes issues in multiscale data analysis and image processing. We then discuss the current state of the multiscale breast imaging research and possible future directions.…”
Section: Review Of Quantitative Multiscale Imaging Of Breast Cancer 1mentioning
confidence: 99%
“…Initially, subjective visual assessments of breast density were made by qualified readers 3 , but computer assisted methods, such as CUMULUS 4 , and volumetric measures, such as Volpara 5 and Quantra 6 , have also been used to measure breast density. No matter which method is used to measure mammographic density, women with the densest breasts are at a 4–6 fold increase in breast cancer risk relative to those with the fattiest breasts 7 .…”
Section: Introductionmentioning
confidence: 99%